Detection and Identification of Detonation Sounds in an Internal Combustion Engine using Wavelet and Regression Analysis - Agus Sujono; R. Soekrisno; Eka Firmansyah; Oyas Wahyunggoro (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Improving efficiency and power in an internal combustion engine is always impeded by detonation (knock) problems. This detonation problem has not been explained fully yet. Quick and accurate detection of detonation is also in the development stage. This research used a new method of detonation sound detection which uses microphone sensors, analysis of discrete wavelet transform (DWT), and analysis of the regression function envelope to identify the occurrence of detonation. The engine sound was captured by the microphone; it was recorded on a computer; it was proceeded using a DWT decomposition filtering technique; it was then subjected to normalization and regression function envelope to get the shape of the wave pattern for the vibration. Vibrational wave patterns were then compared to a reference using the Euclidean distance calculation method, in order to identify and provide an assessment decision as to whether or not detonation had occurred. The new method was applied using Matlab and it has yielded results which are quite effective for the detection and identification of detonation and it is also capable of producing an assessment decision about the occurrance of detonation.